Existence and Ulam stability of initial value problem for fractional perturbed functional q-difference equations - ALLOUCH, Nadia M.G.; HAMANI, Samira (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
In this work, we discuss the existence and uniqueness of solutions to the initial value problem for perturbed functional fractional q-difference equations involving q-derivative of the Caputo sense. By applying Banach contraction principle and Burton and Kirk’s fixed-point theorems. Further, we present the Ulam-Hyers and Ulam-Hyers-Rassias stabilities results by using direct analysis methods. Finally, we give two examples illustrating the results. Mathematics Subject Classification (2010): 26A33, 34A12, 39A13, 47H10. Received 15 March 2022; Accepted 12 September 2022.